On asymptotic behavior of the constants in generalized Khintchine’s inequality - Mykhaylyuk, V. V.; Balan, V. A. (Methods of Functional Analysis and Topology, 2011)
We establish an asymptotic behavior of the constants in Khintchine’s inequality for independent random variables of mean zero.